2020
DOI: 10.21037/jtd-20-1054
|View full text |Cite
|
Sign up to set email alerts
|

Gender effects on quality of life and symptom burden in patients with lung cancer: results from a prospective, cross-cultural, multi-center study

Abstract: Background: Lung cancer causes impairment of health-related quality of life (QoL), but little is known about gender aspects in QoL and symptom burden of lung cancer patients. The aim of this study was to investigate gender differences in QoL as assessed by the European Organization for Research and Treatment of Cancer (EORTC) QLQ-C30 and the updated lung cancer module. Methods: In a prospective, international, cross-cultural, multicenter study that was undertaken to update the lung cancer-specific module EORTC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 31 publications
2
17
1
Order By: Relevance
“…Our analyses showed that female sex was associated with improved survival, worse chemotherapy toxicity, and worse quality of life, findings which are consistent with the existing literature [ 46 48 ]. In our simulated clinical trials, women with advanced age and more comorbidities benefited more from adjuvant chemotherapy than men in the same groups.…”
Section: Discussionsupporting
confidence: 92%
“…Our analyses showed that female sex was associated with improved survival, worse chemotherapy toxicity, and worse quality of life, findings which are consistent with the existing literature [ 46 48 ]. In our simulated clinical trials, women with advanced age and more comorbidities benefited more from adjuvant chemotherapy than men in the same groups.…”
Section: Discussionsupporting
confidence: 92%
“…These findings suggest that sex affects symptom burden and management and should be considered for specific assessment and intervention. 33 , 34 The results from our study showed that poor ECOG status was correlated to both undertreatment and non-treatment of symptoms. Previous studies almost only focused on the relationship between the ECOG status and symptom burden but few studies explored the relationship between ECOG status and symptom management.…”
Section: Discussionmentioning
confidence: 54%
“… 15–21 In contrast an international, multicenter study on lung cancer patients of any tumor stage, using the QLQ-C30 questionnaire and the recently updated lung cancer-specific module the QLQ-LC29, could not find any relevant gender difference regarding QoL. 22–24 …”
Section: Introductionmentioning
confidence: 96%